Determinan Kecurangan Laporan Keuangan dalam Perspektif Fraud Triangle (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI 2020-2022) - Oktaviana, Deva; Maslichah, Maslichah; Hidayati, Irma (e_Jurnal Ilmiah Riset Akuntansi, 2024)
Financial statement fraud is a purposeful inaccuracy meant to mislead those that utilize financial statements, ultimately causing harm to those individuals. The purpose of this study is to ascertain and examine the relationship between financial statement fraud and factors such as audit opinion, inefficient monitoring, personal financial need, external pressure, and financial stability. In food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. Selection of samples in this research was carried out using a purposive sampling method and 36 company data were obtained as samples. Data used is financial report data from companies published via the website www.idx.co.id and the data analysis method used in this research is multiple linear regression, descriptive statistical analysis, normality test, classic assumption test which includes multicollinearity test, autocorrelation test, and heteroscedasticity test. The results of this research show that the variables financial stability, personal financial needs, financial targets, ineffective monitoring have a significant positive effect on financial statement fraud. Whereas, external pressure variables and audit opinion don't significantly impact the falsification of financial statements.Keywords: Financial statement fraud, financial stability, external pressure, personal financial need, financial targets, ineffective monitoring, audit opinion.